Level of Job Satisfaction of Non-teaching Staff at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The chapter presents the background of the study, related literature and related studies,theoretical framework, conceptual framework, statement of the problem, hypothesis, scope,delimitation of the study, the significance of the study, and definition of terms.The results of this study, the study found that the non-teaching staff was female, 21-25 yearsold, had a Bachelor’s degrees, 0-1 years of service, and salary scheme of 10,000-15,000; thelevel of job satisfaction of non-teaching staff were “High” in terms of achievement,responsibilities, recognition, and advancement in terms of job motivators, and ‘’High ‘’ also interms of policy and administration, supervision, work condition, and salary in terms of jobhygiene; there is no significant relationship between the level job satisfaction in terms of jobmotivator and job hygiene of non-teaching staff of Bestlink College of the Philippines; the mostproblems encountered by the non-teaching staff were feel used up at the end of the workday,feel burned out from work, and feel emotionally drained; and there is a proposed guidelines toenhance the job satisfaction of non-teaching staff of Bestlink College of the Philippines.
Keywords: Business